Optimal power allocation for the proposed asymmetric turbo code for 3G systems - Ramasamy, K.; Balamuralithara, B.; Siddiqi, Muhammad Umar (ELSEVIER, 2009)
We proposed a new class of asymmetric turbo encoder for 3G systems that performs well in both “water fall” and “error floor” regions in Ramasamy et al. [Weight distribution analysis of proposed asymmetric turbo code for improved performance, Int J Electron Commun 60(7) 479–93]. In this paper, a modified (optimal) power allocation scheme for the different bits of new class of asymmetric turbo encoder has been investigated to enhance the performance. The simulation results and performance bound for proposed asymmetric turbo code with modified unequal power allocation (UPA) scheme for the frame length, N = 400, code rate, r = 1/3 with log-MAP decoder over additive white Gaussian noise (AWGN) channel are obtained and compared with the system with typical UPA and without UPA. The performance tests are extended over AWGN channel for different frame size to verify the possibility of implementation of the modified UPA scheme for the proposed asymmetric turbo code. From the performance results, it is observed that the proposed asymmetric turbo code with modified UPA performs better than the system without UPA, and with typical UPA and it provides a coding gain of 0.4–0.52 dB.